A new transformerless semi‐quadratic buck–boost converter based on combination of Cuk and traditional buck–boost converters. (13th July 2022) - Hosseinpour, Majid; Ahmadi, Mahsa; Seifi, Ali; Mousavi‐Aghdam, Seyed Reza
Abstract: In this paper, a new transformerless buck–boost converter is proposed. This converter is based on combining two basic converters, including Cuk and traditional buck–boost converters, along with a voltage multiplier (VM) at the output side. The proposed semi‐quadratic buck–boost converter operates in continuous conduction mode (CCM) and provides two operation modes by turning the switches on and off. This converter has some merits such as a wide conversion ratio and continuous input current. The proposed converter consists of two switches with simultaneous operation resulting in simplicity in control. A modular configuration and a wide range of duty cycles are available through the proposed converter, which causes higher or lower output voltage and facilitates the converter maintenance. The calculations of the ideal and the real voltage gain, voltage stress of switches and diodes, efficiency, and design consideration of elements are given in this paper. Finally, a prototype is implemented, and experimental waveforms are obtained to prove and validate the simulation results as well as the theoretical analysis of the proposed converter. Abstract : This paper introduces a new transformerless buck–boost converter, based on combining two basic converters, including Cuk and traditional buck–boost converters, along with a voltage multiplier (VM) at the output side. Compared to a similar reference converter, a wide conversion ratio, continuous input current, and suitable efficiency are the main merits of the proposed converter.